2021
DOI: 10.1007/s11191-021-00261-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Public Engagement with Science on Scientific Information Literacy During the COVID‑19 Pandemic

Abstract: During the COVID-19 pandemic, we are fighting not only the novel coronavirus, but also the “infodemic” induced by the pandemic. Therefore, it is urgent to explore approaches for enhancing individual immunity against science-related misinformation. We conducted a cross-sectional study to examine the relationship between public engagement with science (PES) and scientific information literacy (SIL) during the COVID-19 pandemic from college students (N = 8075) in China. The results showed that there was a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
(42 reference statements)
0
14
1
2
Order By: Relevance
“…After extensive literature review and recording interviews from all the groups and transcribing and comparing the data, we found that strong enough policies do exist to battle almost any hurdle in the way of mass immunization. However, ensuring the proper implementation of these rules is a challenge (5,7,9,11). The results indicate that common hurdles especially illiteracy, overcrowded and poorly organized vaccine centers and less number of available vaccines are the main challenges in mass immunization of Covid 19 (16,19).…”
Section: Discussionmentioning
confidence: 99%
“…After extensive literature review and recording interviews from all the groups and transcribing and comparing the data, we found that strong enough policies do exist to battle almost any hurdle in the way of mass immunization. However, ensuring the proper implementation of these rules is a challenge (5,7,9,11). The results indicate that common hurdles especially illiteracy, overcrowded and poorly organized vaccine centers and less number of available vaccines are the main challenges in mass immunization of Covid 19 (16,19).…”
Section: Discussionmentioning
confidence: 99%
“…The Public Engagement with Science (PES) scale (Gu and Feng, 2022) was deployed to assess their interactions with science as a lay person, which included questions regarding activities and attitudes. The activities subscale included eight items assessing respondents' engagement with science information via media (e.g., books, television, social media), as well as their participation in conversations and conferences discussing science topics measured on a 5-point Likert scale from strongly disagree to strongly agree (Cronbach α = 0.845).…”
Section: Methodsmentioning
confidence: 99%
“…Given the unique application of these scales to a diverse professional population as well as the low reliability of the stereotype subscales, we sought to replicate the findings from the studies from which the measures were sampled. The Public Engagement in Science assessment drew from a college student sample in China (N = 8,075) and found a significant difference between PES activities and PES attitudes; respondents reported significantly greater attitudes about public engagement with science compared to their actual activities engaging with science (Gu and Feng, 2022). This finding was replicated in the current dataset: media professionals reported greater attitudes (M = 3.7, SD = 0.8) than activities (M = 3.6, SD = 0.8); t (104) = 2.4, p = 0.019.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Ya que operan en entornos de enseñanza-aprendizaje, donde los conocimientos se utilizan, generan y transmiten con mayor intensidad, viéndose enfrentados a una enorme responsabilidad, dada la demanda de atención de necesidades de búsqueda y recuperación de información por parte de estudiantes y docentes que confían en el acceso a los servicios que presta biblioteca para mantener continuidad de su formación académica (Nureña, 2019). Sin embargo, en el complejo escenario que nos ofrece la pandemia, una de las grandes barreras es la necesidad de alfabetización informacional (information literacy) en los estudiantes, y esto lo ratifican diversos estudios realizados a estudiantes universidades en distintos continentes en tiempos de pandemia (Fredy, Ary & Mantara, 2020;Gu & Feng, 2021;Hernández-Romero, 2021). De donde surge el peligro de inequidad y desigualdad en la educación digital (Cotino, 2020), lo cual se acentúa en tiempos de Covid-19, más aún en carreras del área de la salud, donde la revisión de evidencia documentada es parte de su filosofía de trabajo (CNA, 2014).…”
Section: Introductionunclassified